2013
DOI: 10.1002/ajhb.22446
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of human milk nutrient composition of women from singapore with a special focus on lipids

Abstract: Collectively, the current observations affirm that HM secretion, especially the lipid composition, is a very dynamic and personalized biological process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
87
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(108 citation statements)
references
References 49 publications
17
87
1
3
Order By: Relevance
“…Although bST was able to overwhelm sex-biased milk synthesis among multiparous cows, significant sex-bias remained among primiparous cows whose mammary glands had functionally developed for the first time in the context of the fetal sex of the first gestation. The magnitude of sex bias is strongest among first parity rhesus monkeys [25][26] and possibly humans [28][29] and Tamar wallabies [31] in which primiparous females have been disproportionately represented in published studies. The effect of fetal sex may diminish to some extent among multiparous females due to the aggregate effects on mammary gland architecture of sequential gestations of different fetal sexes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although bST was able to overwhelm sex-biased milk synthesis among multiparous cows, significant sex-bias remained among primiparous cows whose mammary glands had functionally developed for the first time in the context of the fetal sex of the first gestation. The magnitude of sex bias is strongest among first parity rhesus monkeys [25][26] and possibly humans [28][29] and Tamar wallabies [31] in which primiparous females have been disproportionately represented in published studies. The effect of fetal sex may diminish to some extent among multiparous females due to the aggregate effects on mammary gland architecture of sequential gestations of different fetal sexes.…”
Section: Discussionmentioning
confidence: 99%
“…Suckling behavior, however, is not useful for estimating milk energy transfer as verified by experimental use of radio-labeled isotopes in Equus caballus [22]. Direct evidence for sex-biased milk synthesis among nondomesticated species has now been reported in ungulates (Cervus elaphus hispanicus, [23]), rodents (Myodes glareolus [24]), primates (Macaca mulatta [25][26]; Homo sapiens [27][28][29], but see also [30] for exception), and marsupials (Macropus eugenii, [31]). Drawing systematic conclusions from the studies to date, however, is challenging in part because most have been limited by relatively small sample sizes or report milk composition without accounting for milk yield.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, as our previous work and other studies have observed differences in breast milk composition by infant sex, we also tested for sex interactions. 3,26,27 …”
Section: Introductionmentioning
confidence: 99%
“…All recently published HBM ganglioside data have been generated using high-performance liquid chromatographymass spectrometry (HPLC-MS) techniques [12][13][14][15], given the greater sensitivity and specificity of this technique, whereas earlier data were generated using traditional highperformance thin layer chromatography (HPTLC) methods, which are less sensitive and selective [9,[16][17][18].…”
Section: Introductionmentioning
confidence: 99%